Torus hypersurface in 4-space - Güler, Erhan; Kişi, Ömer; Kişi, Ömer (Ahi Evran Üniversitesi, 2018)
We consider torus hypersurface in the four dimensional Euclideanspace E4. We give some basic notions of E4, then we define rotational hypersur-face. Finally, we define torus hypersurface, and calculate its curvatures with someresults.
Keywords: 4-space; Rotational hypersurface; Torus hypersurface